LATE VALANGINIAN-HAUTERIVIAN RADIOLARIAN AGE CONSTRAINTS FOR SUBDUCTION-RELATED SUBMARINE VOLCANIC ACTIVITY IN THE AMASIA-STEPANAVAN OPHIOLITE (NORTHERN ARMENIA) - Galoyan, Ghazar; Danelian, Taniel; Ojo, Gabriel; Regnier, Sylvie; Atayan, Lusine; Amiraghyan, sona; Grigoryan, Arayik (Ofioliti, 2024)
Radiolarian biochronology of radiolarites associated with ophiolitic lavas in northern Armenia provides important age constraints for the geodynamic reconstruction of Tethys in an area that makes the link between the Lesser Caucasus and the Eastern Pontides. We present results obtained from a moderately well-preserved radiolarian assemblage extracted from radiolarian cherts that crop out in the Bazoum Horst (between Stepanavan and Amasia). The age of these radiolarites may be restricted to the late Valangingian-Hauterivian based on the co-occurrence of the radiolarian species Archaeodictyomitra pseudoscalaris (Tan), Crolanium bipodium (Parona), Pseudodictyomitra suyarii Dumitrica and Tethysetta ovoidala Dumitrica. The dated radiolarites lie stratigraphically ca. 7-8 m above basaltic lavas that have a subduction-related geochemical signature. In combination with results from the Amasia ophiolite, this indicates the presence of a subduction-related island arc at the scale of the Amasia-Stepanavan oceanic realm that was active during Valanginian to Barremian times.